Pathophysiology of Biophoton: Vibrational Impact Syndrome Leading to Physical Effects and Metabolic Alterations. Part 2 - Camelo, Luiz Gonzaga (British Journal of Healthcare and Medical Research, 2025)
Vibrational impact syndrome caused by biophotons is a syndrome resulting from excessive and ultra-weak photon emission. It is worth noting that at the beginning of the clinical picture, the photon emission was diffuse and disseminated, covering several organs and systems, subsequently leading to excessive long-term retention of biophotons, with energy elimination perceived throughout the body surface. This syndrome involves peripheral nerves with changes in electromyography, as well as damage to blood vessels leading to bleeding in the nose, lips and mouth, as well as damage to the saphenous vein in the right leg and metabolic changes, such as elevated blood levels of triglycerides, cholesterol, fasting glucose and testosterone, as well as a reduction in Vitamin B12 that can damage peripheral nerves. Furthermore, in August 2024, Prostaglandin E2 was measured with a significant increase, with titers above 4,000%, leading to several clinical implications. In fact, this is a case report in a 72-year-old patient with pathological photon emission for 10 years that persists to this day. I assume this is the first study reported in the literature and the most surprising, reported by the patient and also the author of this essay who, fortunately, is a physician. It arose spontaneously and without interference from any external factor. However, there appears to have been internal interference. In fact, it appeared a week after his wife underwent breast cancer surgery. Here it became clear that the role of Consciousness in the emission of biophotons is unquestionable. It follows an intelligent and intentional pattern. Consciousness, the Intelligent Principle of the Universe, is the product of Universal Consciousness, the Supreme Intelligence of the Universe, the first cause of all things. It is undoubtedly the one that actually absorbs and metabolizes the photon captured from the sun, which ultimately comes from the “sea of ​​energy” called the ‘zero-point quantum field’ [ZPF] studied by contemporary science.